Pharmacological Studies on the Role of 5-HT1A Receptors in Male Sexual Behavior of Wildtype and Serotonin Transporter Knockout Rats - Esquivel-Franco, Diana Carolina; de Boer, Sietse F.; Waldinger, Marcel; Olivier, Berend; Olivier, Jocelien D. A. (Frontiers in Behavioral Neuroscience, 2020)
Brain serotonin (5-HT) neurotransmission plays an important role in male sexual behavior and it is well established that activating 5-HT1AR in rats facilitates ejaculatory behavior. However, the relative contribution of 5-HT1A somatodendritic autoreceptors and heteroreceptors in this pro-sexual behavior is unclear. Moreover, it is unclear whether the contribution of somatodendritic 5-HT1A autoreceptors and postsynaptic 5-HT1A heteroreceptors alter when extracellular 5-HT levels are chronically increased. Serotonin transporter knockout (SERT-/-) rats exhibit enhanced extracellular 5-HT levels and desensitized 5-HT1A receptors. These rats model neurochemical changes underlying chronic SSRI-induced sexual dysfunction. We want to determine the role of presynaptic versus postsynaptic 5-HT1A receptors in the pro-sexual effects of 5-HT1A receptor agonists in SERT+/+ and in SERT-/- rats. Therefore, acute effects of the biased 5-HT1A receptor agonists F-13714, a preferential 5-HT1A autoreceptor agonist, or F-15599, a preferential 5-HT1A heteroreceptor agonist, and S15535 a mixed 5-HT1A autoreceptor agonist/heteroreceptor antagonist, on male sexual behavior were assessed. A clear and stable genotype effect was found after training where SERT+/+ performed sexual behavior at a higher level than SERT-/- rats. Both F-15599 and F-13714 induced pro-sexual activity in SERT+/+ and SERT-/- animals. Compared to SERT+/+, the F13714- dose-response curve in SERT-/- rats was shifted to the right. SERT+/+ and SERT-/- rats responded similar to F15599. Within both SERT+/+ and SERT-/- rats the potency of F-13714 was much stronger compared to F-15599. S15535 had no effect on sexual behavior in either genotype. In SERT+/+ and SERT-/- rats that were selected on comparable low sexual activity (SERT+/+ 3 or less ejaculations and SERT-/- 5 or less ejaculations in 10 weeks) S15535 also did not influence sexual behavior. The two biased compounds with differential effects on 5-HT1A auto- and hetero-receptors, exerted pro-sexual activity in both SERT+/+ and SERT-/- rats. Applying these specific pharmacological tools has not solved whether pre- or post-synaptic 5-HT1A receptors are involved in pro-sexual activity. Moreover, the inactivity of S15535 in male sexual behavior in either genotype was unexpected. The question is whether the in vivo pharmacological profile of the different 5-HT1A receptor ligands used, is sufficient to differentiate pre-and/or post-synaptic 5-HT1AR contributions in male rat sexual behavior.